The Effect Of Digital Marketing Brand Image On Trust And Its Impact On The Decision To Visit The Dentist - Antonius Hartanto; Probo Asmoro; Achmad Baihaqi Junaedi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
This study aimed to determine the effect of digital marketing brand image on trust and its impact on visiting the dentist. The research method used in this study is a quantitative method using PLS data analysis. Sampling used a nonprobability sampling technique, namely purposive sampling, on residents of Malang who had visited the dentist as many as 100 respondents. The research found that: 1) brand image has a significant positive effect on customer trust, 2) brand image has a significant positive effect on visiting decisions, 3) digital marketing has a significant positive effect on customer trust, 4) digital marketing has a significant positive effect on customer visiting decisions, 5) customer trust has a significant positive effect on visiting decisions